An Interesting Case of Double Compound Intussusception without Intestinal Occlusion in a 5-Year-Old Boy - Destro, Francesca; Cantone, Noemi; Maffi, Michela; Gargano, Tommaso; Lima, Mario (European Journal of Pediatric Surgery Reports, 2014)
Intussusception is a very common surgical finding in children. Idiopathic intussusception is relatively frequent in children within the first year and it usually causes an acute abdomen. Instead, complex intussusception involving multiple or remote intestinal segments is a very rare entity and it is frequently diagnosed intraoperatively. It is often because of an anatomical cause and it can occur at any age. We report a unique case of contemporary double site anterograde and retrograde ileoileal intussusception without intestinal occlusion because of a submucous intestinal lipoma. In our case, imaging studies were important for clinical suspicion and laparoscopy was essential for final diagnosis and its resolution.
Keywords: compound intussusception; children; laparoscopy